Cover Image, Volume 530, Issue 7. Issue 7 (25th March 2022) - Sokhadze, Guela; Campbell, Peter W.; Charalambakis, Naomi; Govindaiah, Gubbi; Guido, William; McGee, Aaron W.
Abstract : The cover image is based on the Research Article "Cre driver mouse lines for thalamocortical circuit mapping", by Sokhadze et al. https://doi.org/10.1002/cne.25248 . It depicts coronal brain sections from two transgenic mouse lines (Left: Crh‐Cre KN282. Right: HDC‐Cre ) that target expression of Cre recombinase to thalamocortical neurons. The somata and processes of thalamocortical neurons are visualized by crossing these strains to a red fluorescent reporter line CAG‐tdTomato (AI9).